Mitigation of Operational Shortcomings in an Isamill through Design Change- A Numerical Perspective - S. Sahu; N. K. V. Nadimpalli; V. Runkana (International Mineral Processing Congress, 2018)
"IsaMill™ has been in operation in the recent past for fine grinding of low grade ores to extract non-ferrous minerals. IsaMill™, typically, consists of a series of uniformly spaced identical disks mounted on a rotating shaft which is encased in an outer shell. The mill offers high energy efficiency for fine grinding and an inherent scalability. But, it encounters certain operational challenges such as non-uniform distribution of grinding media coupled with high wear rate of the disks and solid walls of the mill at specific locations—which adversely affect the mill performance. To circumvent these operational challenges, design modification of the disks through heuristics, by introducing a reduced diameter disk (RDD) at specific locations, is a common practice in industry. But there is no systematic scientific study in this regard. In the current work, we developed a discrete element method (DEM) based model and simulated for the IsaMill™ operation to study the effect of RDD on the efficiency of the mill and wear rate of the solid walls and disks. Since the first set of disks experience the high wear rate due to the high loading of the charge, the RDD was introduced at the first two disks. The simulations were performed at different diameters of the RDDs and at different media loadings. The performance of the mill was analyzed based on the power consumption, the wear rate on disks and the distribution of media particles inside the mill. Besides, the performance variables such as mean velocity of media particles and total impact energy provided useful insights into the milling operation. It was observed that the reduction in disk diameter yields lower wear rate of the disks at the cost of decrease in power draw at a constant high media loading. Whereas, when the media loading was decreased, the amount of wear and power drawn was comparable for both the most reduced and least reduced disk diameters. Therefore, there is an optimum choice of RDD for a given mill loading to maximize the mill performance while reducing the wear rate of the disks."